The Effect of Brain-Based Learning (BBL) Model with Audiovisual Media on Student's High-Level Thinking Ability - Gita Dwi Wardani; Retno Dwi Suyanti; Daulat Saragi (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this study was to obtain scientific information about students' higher-order thinking skills with the Brain-Based Learning (BBL) learning model using audiovisual media guided by students' learning motivation to develop teaching materials, especially in science subjects